#TITLE_ALTERNATIVE# - RIZKY YUDIANSYAH (NIM :12208061), ANDY
Knowledge of well performance and reservoir properties, such as permeability, skin, reserves and drainage area, are very important in determining strategies and optimization for gas field development. There were many methods that have been used to earn those data. However, most of them require long shutting in period which may impact to company's revenue. Conventional method like well testing (pressure build-up and pressure draw down) may cost quite expensive. Meanwhile, reserve estimation using material balance also requires accurate reservoir pressure data within long period of time. On the other hand, production data might always be available and ready-to-use. This data can be used to determine the unknown reservoir parameters such as permeability, reserves, skin, and drainage area by using type curve. Each type curve is normally developed for a constant bottom hole pressure. But in real condition, the bottom hole pressure may vary due to the application of development strategies. Furthermore, this codition could reduce the accuracy of type curve utilization. A modified type curve based on J.Ansah's work is proposed to accomodate variable bottom hole pressure condition. The modification was based on the first order polynomial model. The proposed model was validated using a commercial reservoir simulator CMG and the results were in a very good agreement.